Maize resistance to witchweed through changes in strigolactone biosynthesis - Changsheng Li; Dong, Lemeng; Durairaj, Janan; Guan, Jiahn-Chou; Yoshimura, Masahiko; Quinodoz, Pierre; Horber, Robin; Gaus, Katharina; Jing Li; Setotaw, Yohannes Besufekad; Qi, Jinfeng; Groote, Hugo de; et al. (American Association for the Advancement of Science, 2023)
Maize (Zea mays) is a major staple crop in Africa, where its yield and the livelihood of millions are compromised by the parasitic witchweed Striga. Germination of Striga is induced by strigolactones exuded from maize roots into the rhizosphere. In a maize germplasm collection, we identified two strigolactones, zealactol and zealactonoic acid, which stimulate less Striga germination than the major maize strigolactone, zealactone. We then showed that a single cytochrome P450, ZmCYP706C37, catalyzes a series of oxidative steps in the maize-strigolactone biosynthetic pathway. Reduction in activity of this enzyme and two others involved in the pathway, ZmMAX1b and ZmCLAMT1, can change strigolactone composition and reduce Striga germination and infection. These results offer prospects for breeding Striga-resistant maize.